Effectiveness of Creative Thinking Instruments Through Discovery Learning Models in Improving Creative Thinking Skills - Ai Nur Solihat; Dadang Dahlan; Kusnendi Kusnendi; Budi Susetyo (Jurnal Inovasi Pendidikan Ekonomi (JIPE), 2024)
This study aims to analyze the need, feasibility, and effectiveness of creative thinking instruments in economic learning. The study procedures were carried out using Research and Development (R&D) method, which comprised various stages, including planning, development, feasibility testing, and instrument implementation. Subsequently, a needs analysis was performed by distributing questionnaires and conducting interviews with economics subject teachers. Content validity testing was also carried out through Focus Group Discussion (FGD) with nine experts in economics learning, followed by analysis using Aiken Validity Index (Aiken V-Index). Reliability analysis was performed using KR20 through limited tests on 32 class X students at SMAN 4 Bandung City. Confirmatory Factor Analysis (CFA) was used to test the feasibility of the question items. To test the instrument's effectiveness, a quasi-experiment with the one-group pretest-posttest design was conducted on 37 students in class X at SMAN 1 Tasikmalaya City. The results showed that 70.8% of economics teachers expressed a demand for the development of creative thinking instruments. Among the 60 items developed, 47 were declared feasible based on CFA results. In addition, a total of 47 items were implemented through the discovery learning model. The results of hypothesis testing showed that the discovery learning model using the developed instrument proved effective in improving students' creative thinking skills in economics.